#DigPed Narratives in Education: Critical Perspectives on Power and Pedagogy - Suzan Koseoglu; Aras BOZKURT (Online Learning, 2018)
This mixed methods study addresses a knowledge gap in the nature and effects of networked scholarship. We analyze #DigPed, a Twitter hashtag on critical pedagogy, through the lens of Tufekci’s Capacities and Signals framework in order to understand (1) how educational narratives develop and spread on #DigPed, and (2) the nature of their capacities. Using Social Network Analysis and thematic analysis of content, we identify three prominent narratives in the network and discuss the network structures from a critical perspective. Based on the findings, we propose pedagogic capacity—the power to initiate a productive and potentially transformative educational discourse, within one’s self and within communities—as an additional lens to explore the spread and impact of critical narratives in education. Findings confirm the view that networked spaces are organized by hidden hierarchies marked by influence.